Efektivitas Pengelolaan Manajemen Anggaran yang dilaksanakan Komisi V DPRD Provinsi Jawa Barat Terhadap Mitra Kerja Komisi - Panjaitan, Angel; Darmawan, Eki Dudi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
In this scientific article and supported by some data that shows the effectiveness of Commission V of the West Java Provincial DPRD in managing budget management, where the budget management managed by Commission V of the West Java Provincial DPRD is the Regional Budget (APBD). Descriptive method is a method that aims to produce data that is in accordance with the description or description systematically, factually and accurately about the facts, properties and have a relationship between the phenomena studied. In this research the author tries to be able to analyze, interpret, and describe the problems that occur and then after that draw conclusions from these problems regarding the effectiveness of budget management management of working partners of Commission V of the West Java Provincial DPRD. The author chooses data collection techniques by conducting interviews and documentation, and the data taken for this study are data sourced from documents and interviews with people directly involved in budget management activities, namely Commission V of the West Java Provincial DPRD and using data in the form of literature studies sourced from journals, laws and regulations, and other influencing factors then presented in written form systematically. Commission V of the West Java Provincial DPRD has a very important role in managing budget management, where Commission V has activities and main tasks for the development of Social Welfare, namely work visits, meeting procurement, carrying out management processes and supervising the implementation of the APBD so that supervision carried out by Commission V can be more effective and efficient and can obtain maximum results in each year. Keywords: Budgetting; DPRD; Commission V DPRD; Working Partners.